Anti-Ro/SSA antibodies and cardiac rhythm disturbances: Present and future perspectives. (1st April 2015) - Santos-Pardo, Irene; Villuendas, Roger; Salvador-Corres, Iñaki; Martínez-Morillo, Melania; Olivé, Alejandro; Bayes-Genis, Antoni
Abstract: Several case reports, small case series, and original research papers have recently suggested that the action of certain auto-antibodies related to connective tissue diseases may be responsible for significant cardiac rhythm disturbances in adults. The relationship between anti-Ro/SSA antibodies and congenital complete atrioventricular block is well recognized in the fetal heart. Herein we review the emerging evidences of the link to increased levels of anti-Ro/SSA antibodies with rhythm disorders of unknown origin in the adult. Confirmation of this distinct etiology may eventually be the basis for new therapies. Highlights: Certain antibodies could be the pathogenic basis of cases of heart block. Immunosuppressive therapy may have a role in preventing the need for pacing. These antibodies have also been linked to prolongation in cardiac repolarization.